Carbon-ceramic brake disc containing friction layer and preparation method of carbon-ceramic brake disc
Through laser pretreatment, uniform triangular and quadrangular friction layer units are formed, combined with the synthesis of silicon carbide particles and phenolic resin and silicon permeation treatment, the problem of uneven cracks in the friction layer of the carbon ceramic brake disc is solved, and the wear resistance of the brake disc is improved and friction layer stability.
Patent Information
- Application Number
- CN202411325885.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-20
AI Technical Summary
Due to the difference in thermal expansion coefficient of the friction layer of the carbon ceramic brake disc, it is easy to produce uneven cracks, resulting in local stress concentration during friction and peeling off the friction layer, affecting the wear resistance of the brake disc.
Triangular and quadrangular friction layer units are formed through laser pretreatment, which optimizes the crack distribution to make it more uniform, increases the stability of the friction layer, and uses silicon carbide particles and phenolic resin to synthesize the friction layer during the preparation process, combined with silicone permeation treatment to improve The wear resistance of the brake disc.
It significantly improves the stability of the friction layer, prevents the friction layer from peeling off, improves the wear resistance of the brake disc and the stability of the friction coefficient, simplifies the preparation process, and is suitable for large-scale production.
Smart Images

Figure BDA0005055405650000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake disc manufacturing, and in particular to a carbon-ceramic brake disc containing a friction layer and a preparation method thereof. Background Art
[0002] The brake disc is an important component installed on vehicles such as cars and motorcycles, used to brake the vehicle. It is usually located between the wheels and works with the brake calipers, brake pads, etc. in the brake system. The brake disc mainly plays the role of deceleration or emergency stop during the operation of the car. It is related to human life safety in emergencies, so it is particularly important. Brake discs are divided into two common types: metal brake discs and carbon ceramic brake discs. Metal brake discs are usually made of cast iron, steel or aluminum alloy, and are durable and have high braking performance. Carbon ceramic brake discs are made of carbon fiber and ceramic materials, and are lighter, have higher braking performance and wear resistance, and are suitable for high-performance vehicles.
[0003] At present, the preparation process of carbon ceramic brake discs is needle puncture-carbonization-high temperature treatment-chemical vapor deposition-high temperature treatment-application of friction layer-processing-siliconization-processing, wherein the friction layer is set to improve the wear resistance of the brake disc and stabilize the friction coefficient. Due to the difference in thermal expansion coefficients between the friction layer and the brake disc, cracks are easily generated in the friction layer, and the size and shape of the cracks generated in the friction layer are uneven due to the uneven distribution of the physical phases. During friction, large stress is easily generated locally, resulting in the peeling of the friction layer. In this regard, a carbon ceramic brake disc containing a friction layer is proposed, which effectively increases the uniformity of crack distribution in the friction layer and greatly improves the stability of the friction layer during friction. Summary of the invention
[0004] The purpose of the present invention is to provide a carbon-ceramic brake disc containing a friction layer and a preparation method thereof. In view of the uneven distribution of cracks in the friction layer, laser pretreatment is used to increase the uniformity of crack distribution in the friction layer, thereby greatly improving the stability of the friction layer during friction.
[0005] To achieve this purpose, the present invention provides a carbon ceramic brake disc with a friction layer, the carbon ceramic brake disc with a friction layer comprising a base layer and a friction layer arranged on the outer surface of the base layer. The friction layer surface has a plurality of cracks, and adjacent cracks are interconnected to form a friction layer unit, the friction unit comprises a triangular friction layer unit and a four-corner friction layer unit; the triangular friction layer unit is formed by three cracks connected and surrounded, and the four-corner friction layer unit is formed by four cracks connected and surrounded; the area of the triangular friction layer unit is 2-15mm 2 The area of the four-corner friction layer unit is 5-20mm 2 .
[0006] Preferably, the number of the triangular friction layer units accounts for 5-30% of the total number of friction layer units, and the number of the quadrangular friction layer units accounts for 70-95% of the total number of friction layer units.
[0007] Preferably, the friction layer has a thickness of 0.5-3 mm.
[0008] Preferably, the width of the crack is 10-100 μm.
[0009] Preferably, the friction layer contains coarse silicon carbide particles with a particle size of 80-150 microns and fine silicon carbide particles with a particle size of 0.5-30 microns, and the content ratio of the coarse silicon carbide particles to the fine silicon carbide particles is 1:1 to 10:1.
[0010] Preferably, the silicon carbide content in the friction layer is 50-80%, and the silicon content is 20-50%.
[0011] The present invention also provides a method for preparing a carbon-ceramic brake disc containing a friction layer, which is used to prepare the carbon-ceramic brake disc containing a friction layer, comprising the following steps:
[0012] S1: preparing a carbon fiber preform of a predetermined thickness;
[0013] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;
[0014] S3: Carbonizing the impregnated body to obtain a carbonized body, the carbonization temperature is 800-1100° C., and the temperature is kept for 4-6 hours;
[0015] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1400-1800° C., and the temperature is kept for 2 hours;
[0016] S5: mixing silicon carbide and phenolic powder evenly to obtain friction layer pressed powder, evenly laying it on the graphitized blank, and then pressurizing at a pressure of 0.5-4 MPa and a temperature of 150° C. for 60 minutes to completely solidify it to obtain a brake disc preform;
[0017] S6: laser engraving the friction layer on the surface of the brake disc preform according to a desired pattern, with an engraving depth of 0.05-0.2 mm, and after engraving, machining to obtain a brake disc preform;
[0018] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa;
[0019] S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
[0020] Preferably, the carbon fiber unidirectional cloth and the carbon fiber mesh are stacked as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at an angle of 90°, and after stacking one unit, the sample is needle-punched, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of the desired thickness, and the needle-punching density is 50-200 needles / cm 2 .
[0021] Preferably, the steps S2 and S3 are performed at least once to make the density of the carbonized body reach 1.25-1.45 g / cm 3 .
[0022] Preferably, the particle size of silicon carbide in the friction layer pressed powder is 80-150 microns, the content is 45-75 vol%, and the phenolic powder is 25-55 vol%.
[0023] Beneficial effect: The carbon-ceramic brake disc with a friction layer provided by the present invention aims to solve the problem that cracks are easily generated in the friction layer due to the difference in thermal expansion coefficients between the friction layer and the brake disc, and the uneven crack shape is easy to generate large stress locally, resulting in the peeling of the friction layer. By planning the crack position and shape of the friction layer, the cracks are connected in the friction layer to form a triangular friction layer unit or a four-corner friction layer unit. Compared with the irregular crack distribution, the uniformly distributed cracks can make the friction layer have better stability, prevent the peeling of the friction layer caused by excessive local force during friction, and have great significance for improving the wear resistance of the brake disc. The four-corner friction unit has a larger angle, and is less likely to have stress concentration in the crack unit during friction than the triangular friction unit, which can avoid the peeling of the friction unit. However, the four-corner friction unit is difficult to exist alone, and is generally accompanied by a triangular friction unit. By adjusting the proportion of the four-corner friction unit and the triangular friction unit, the wear resistance of the friction layer of the brake disc can be balanced.
[0024] The present invention also proposes a method for preparing a carbon-ceramic brake disc containing a friction layer. The entire preparation process is simple, and laser engraving is used to pre-treat the friction layer. A pattern is engraved on a siliconized friction blank. After siliconization, cracks in the friction layer are preferentially distributed along the pre-processed pattern, which effectively increases the uniformity of the crack distribution in the friction layer and avoids the random and disordered distribution of cracks in the friction layer prepared by traditional processes. The process is relatively low in difficulty and is easy to mass produce. DETAILED DESCRIPTION
[0025] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] This embodiment provides a carbon ceramic brake disc with a friction layer, the carbon ceramic brake disc with a friction layer includes a base layer and a friction layer arranged on the outer surface of the base layer. The friction layer surface has a plurality of cracks, and adjacent cracks are interconnected to form a friction layer unit, the friction unit includes a triangular friction layer unit and a four-corner friction layer unit; the triangular friction layer unit is surrounded by three cracks, and the four-corner friction layer unit is surrounded by four cracks; the area of the triangular friction layer unit is 2-15mm 2 The area of the four-corner friction layer unit is 5-20mm 2 .
[0027] The number of the triangular friction layer units accounts for 5-30% of the total number of friction layer units, and the number of the quadrangular friction layer units accounts for 70-95% of the total number of friction layer units.
[0028] The friction layer has a thickness of 0.5-3 mm.
[0029] The width of the crack is 10-100 μm.
[0030] The friction layer contains coarse silicon carbide particles with a particle size of 80-150 microns and fine silicon carbide particles with a particle size of 0.5-30 microns, and the content ratio of the coarse silicon carbide particles to the fine silicon carbide particles is 1:1 to 10:1. The content ratio of the coarse silicon carbide particles to the fine silicon carbide particles includes but is not limited to 1:1 or 2:1 or 3:1 or 4:1 or 5:1 or 6:1 or 7:1 or 8:1 or 9:1 or 10:1.
[0031] The silicon carbide content in the friction layer is 50-80%, and the silicon content is 20-50%.
[0032] The present invention also provides a method for preparing a carbon-ceramic brake disc containing a friction layer, comprising the following steps:
[0033] S1: preparing a carbon fiber preform of a predetermined thickness;
[0034] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body;
[0035] S3: Carbonizing the impregnated body to obtain a carbonized body, the carbonization temperature is 800-1100° C., and the temperature is kept for 4-6 hours;
[0036] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1400-1800° C., and the temperature is kept for 2 hours;
[0037] S5: mixing silicon carbide and phenolic powder evenly to obtain friction layer pressed powder, evenly laying it on the graphitized blank, and then pressurizing at a pressure of 0.5-4 MPa and a temperature of 150° C. for 60 minutes to completely solidify it to obtain a brake disc preform;
[0038] S6: laser engraving the friction layer on the surface of the brake disc preform according to a desired pattern, with an engraving depth of 0.05-0.2 mm, and after engraving, machining to obtain a brake disc preform;
[0039] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa;
[0040] S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
[0041] The method for preparing the carbon fiber preform comprises: stacking the carbon fiber unidirectional cloth and the carbon fiber web as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90 degrees, and after stacking one unit, acupuncture is performed on the sample, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of a desired thickness, wherein the acupuncture density is 50-200 needles / cm 2 .
[0042] Step S2 and step S3 are performed at least once, so that the density of the carbonized body reaches 1.25-1.45 g / cm 3 .
[0043] The particle size of silicon carbide in the friction layer pressed powder is 80-150 microns, the content is 45-75 vol%, and the phenolic powder is 25-55 vol%.
[0044] Example 1
[0045] This embodiment provides a carbon-ceramic brake disc with a friction layer, and a preparation method thereof comprises the following steps:
[0046] S1: The carbon fiber unidirectional cloth and the carbon fiber mesh are stacked as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at a 90° angle, and after stacking one unit, the sample is needle-punched, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of the desired thickness, and the needle-punching density is 150 needles / cm 2 ;
[0047] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform until the alcohol is completely volatilized to obtain an impregnated body;
[0048] S3: Carbonizing the impregnated body to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours, and then impregnating the carbonized body again, repeating steps S2 and S3 until the density of the carbonized body reaches 1.4 g / cm 3 ;
[0049] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1700° C., and the temperature is kept for 2 hours;
[0050] S5: Silicon carbide and phenolic powder are mixed evenly to obtain friction layer pressed powder, which is evenly laid on the graphitized blank, and then pressed at a pressure of 2 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform, wherein the silicon carbide particle size in the friction layer pressed powder is 100 μm, the content is 60 vol%, and the phenolic powder is 40 vol%, and the thickness of the friction layer after pressing is 0.8 mm;
[0051] S6: The friction layer solidified on the surface of the brake disc preform is laser engraved according to the required pattern, with an engraving depth of 0.1 mm, wherein the unit area of the pre-engraved triangular friction layer is 9 mm 2 , accounting for 23% of the total number, and the unit area of the pre-carved four-corner friction layer is 18mm 2 , accounting for 77% of the total number. After engraving, mechanical processing is performed to prepare the ventilation ducts and other features of the product to obtain the brake disc blank;
[0052] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;
[0053] S8: performing surface grinding and outer contour dimension processing on the silicided body to obtain the carbon-ceramic brake disc containing the friction layer.
[0054] Example 2
[0055] This embodiment provides a carbon-ceramic brake disc with a friction layer, and a preparation method thereof comprises the following steps:
[0056] S1: The carbon fiber unidirectional cloth and the carbon fiber mesh are stacked as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at a 90° angle, and after stacking one unit, the sample is needle-punched, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of the desired thickness, and the needle-punching density is 150 needles / cm 2 ;
[0057] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform until the alcohol is completely volatilized to obtain an impregnated body;
[0058] S3: Carbonizing the impregnated body to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours, and then impregnating the carbonized body again, repeating steps S2 and S3 until the density of the carbonized body reaches 1.4 g / cm 3 ;
[0059] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1700° C., and the temperature is kept for 2 hours;
[0060] S5: Silicon carbide and phenolic powder are mixed evenly to obtain friction layer pressed powder, which is evenly laid on the graphitized blank, and then pressed at a pressure of 2 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform, wherein the silicon carbide particle size in the friction layer pressed powder is 100 μm, the content is 60 vol%, and the phenolic powder is 40 vol%, and the thickness of the friction layer after pressing is 0.8 mm;
[0061] S6: The friction layer solidified on the surface of the brake disc preform is laser engraved according to the required pattern, with an engraving depth of 0.1 mm, wherein the unit area of the pre-engraved triangular friction layer is 15 mm 2 , accounting for 23% of the total number, and the unit area of the pre-carved four-corner friction layer is 28mm 2 , accounting for 77% of the total number. After engraving, mechanical processing is performed to prepare the ventilation ducts and other features of the product to obtain the brake disc blank;
[0062] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;
[0063] S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
[0064] Example 3
[0065] This embodiment provides a carbon-ceramic brake disc with a friction layer, and a preparation method thereof comprises the following steps:
[0066] S1: The carbon fiber unidirectional cloth and the carbon fiber mesh are stacked as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at a 90° angle. After stacking one unit, the sample is needle-punched, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of the desired thickness. The needle-punching density is 150 needles / cm 2 ;
[0067] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform until the alcohol is completely volatilized to obtain an impregnated body;
[0068] S3: Carbonizing the impregnated body to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours, and then impregnating the carbonized body again, repeating steps S2 and S3 until the density of the carbonized body reaches 1.4 g / cm 3 ;
[0069] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1700° C., and the temperature is kept for 2 hours;
[0070] S5: Silicon carbide and phenolic powder are mixed evenly to obtain friction layer pressed powder, which is evenly laid on the graphitized blank, and then pressed at a pressure of 2 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform, wherein the silicon carbide particle size in the friction layer pressed powder is 100 μm, the content is 60 vol%, and the phenolic powder is 40 vol%, and the thickness of the friction layer after pressing is 0.8 mm;
[0071] S6: The friction layer solidified on the surface of the brake disc preform is laser engraved according to the required pattern, with an engraving depth of 0.1 mm, wherein the unit area of the pre-engraved triangular friction layer is 9 mm 2 , the number accounts for 20%, and the unit area of the pre-carved four-corner friction layer is 18mm 2, accounting for 80% of the total number, after engraving, mechanical processing is carried out to prepare the ventilation ducts and other features of the product to obtain the brake disc blank;
[0072] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;
[0073] S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
[0074] Example 4
[0075] This embodiment provides a carbon-ceramic brake disc with a friction layer, and a preparation method thereof comprises the following steps:
[0076] S1: The carbon fiber unidirectional cloth and the carbon fiber mesh are stacked as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at a 90° angle. After stacking one unit, the sample is needle-punched, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of the desired thickness. The needle-punching density is 150 needles / cm 2 ;
[0077] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform until the alcohol is completely volatilized to obtain an impregnated body;
[0078] S3: Carbonizing the impregnated body to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours, and then impregnating the carbonized body again, repeating steps S2 and S3 until the density of the carbonized body reaches 1.4 g / cm 3 ;
[0079] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1700° C., and the temperature is kept for 2 hours;
[0080] S5: Silicon carbide and phenolic powder are mixed evenly to obtain friction layer pressed powder, which is evenly laid on the graphitized blank, and then pressed at a pressure of 2 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform, wherein the silicon carbide particle size in the friction layer pressed powder is 100 μm, the content is 60 vol%, and the phenolic powder is 40 vol%, and the thickness of the friction layer after pressing is 0.8 mm;
[0081] S6: The friction layer solidified on the surface of the brake disc preform is laser engraved according to the required pattern, with an engraving depth of 0.1 mm, wherein the unit area of the pre-engraved four-corner friction layer is 28 mm 2 , accounting for 100% of the total number, after engraving, mechanical processing is carried out to prepare the ventilation ducts and other features of the product to obtain the brake disc blank;
[0082] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;
[0083] S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
[0084] Example 5
[0085] This embodiment provides a carbon-ceramic brake disc with a friction layer, and a preparation method thereof comprises the following steps:
[0086] S1: stacking carbon fiber unidirectional cloth and carbon fiber web as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90°, and after stacking one unit, acupuncture the sample, and repeatedly stacking unit layers to obtain a carbon fiber preform of a desired thickness, wherein the acupuncture density is 150 needles / cm2;
[0087] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform until the alcohol is completely volatilized to obtain an impregnated body;
[0088] S3: Carbonizing the impregnated body to obtain a carbonized body at a carbonization temperature of 900° C. for 6 hours, and impregnating the carbonized body again, repeating steps S2 and S3 until the density of the carbonized body reaches 1.4 g / cm3;
[0089] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1700° C., and the temperature is kept for 2 hours;
[0090] S5: Silicon carbide and phenolic powder are mixed evenly to obtain friction layer pressed powder, which is evenly laid on the graphitized blank, and then pressed at a pressure of 2 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform, wherein the silicon carbide particle size in the friction layer pressed powder is 100 μm, the content is 60 vol%, and the phenolic powder is 40 vol%, and the thickness of the friction layer after pressing is 0.8 mm;
[0091] S6: The friction layer solidified on the surface of the brake disc preform is laser engraved according to the required pattern, with an engraving depth of 0.1 mm, wherein the unit area of the pre-engraved triangular friction layer is 15 mm 2 , accounting for 100% of the total number, after engraving, mechanical processing is carried out to prepare the ventilation ducts and other features of the product to obtain the brake disc blank;
[0092] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;
[0093] S8: performing surface grinding and outer contour dimension processing on the silicided body to obtain the carbon-ceramic brake disc containing the friction layer.
[0094] Comparative Example 1
[0095] This comparative example provides a carbon ceramic brake disc containing a friction layer, and the preparation method thereof comprises the following steps:
[0096] S1: The carbon fiber unidirectional cloth and the carbon fiber mesh are stacked as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloths of two adjacent unit layers are at a 90° angle, and after stacking one unit, the sample is needle-punched, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of the desired thickness, and the needle-punching density is 150 needles / cm 2 ;
[0097] S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform until the alcohol is completely volatilized to obtain an impregnated body;
[0098] S3: Carbonizing the impregnated body to obtain a carbonized body at a carbonization temperature of 900°C for 6 hours, and then impregnating the carbonized body again, repeating steps S2 and S3 until the density of the carbonized body reaches 1.4 g / cm 3 ;
[0099] S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1700° C., and the temperature is kept for 2 hours;
[0100] S5: Silicon carbide and phenolic powder are mixed evenly to obtain friction layer pressed powder, which is evenly laid on the graphitized blank, and then pressed at a pressure of 2 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform, wherein the silicon carbide particle size in the friction layer pressed powder is 100 μm, the content is 60 vol%, and the phenolic powder is 40 vol%, and the thickness of the friction layer after pressing is 0.8 mm;
[0101] S6: Mechanically processing the brake disc preform to prepare features such as ventilation channels of the product to obtain a brake disc preform;
[0102] S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;
[0103] S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
[0104] The carbon ceramic brake discs containing friction layers prepared in the above-mentioned Examples 1-5 and Comparative Example 1 were tested. The dynamic friction coefficient and wear rate of the carbon ceramic brake disc samples were tested using an MM-1000 friction tester. The effective friction surface of the test ring had an outer diameter of D75mm / inner diameter of D55mm×10mm, and a specific pressure of 98N / cm 2 , inertia is 3kgf·cm·s 2 , linear speed is 25m / s.
[0105] The test data is shown in Table 1.
[0106] Table 1 Test data of carbon ceramic brake discs containing friction layers prepared in Examples 1-5 and Comparative Example 1
[0107]
[0108] From the above examples and comparative data, it can be seen that from examples 1 and 2, as the area of the friction layer unit increases, the wear amount increases. The area of pre-laser processing increases, but after siliconizing and cooling, new cracks will be generated in the prefabricated crack unit, resulting in an increase in the number of triangular friction layer units compared to laser processing, and a decrease in the number of four-corner friction layer units, resulting in a slight increase in the wear amount during friction, and an increase in the fluctuation of the friction coefficient;
[0109] It can be seen from Example 3 and Example 1 that as the proportion of the four-corner friction layer units increases, the stability of the friction coefficient increases and the wear rate also decreases.
[0110] From the data of Example 4, it can be seen that when the laser pre-patterning is performed, the friction layer units are all quadrangular, but after siliconization, 5% of the friction layer units still appear. Although the stability of the friction coefficient is improved and the wear amount is reduced, the difference between the maximum and minimum crack areas will become larger, and its uniformity will be reduced.
[0111] It can be seen from Example 5 that the laser pre-processing is all triangular units, and the peeling condition during friction becomes more obvious, resulting in a significant increase in the friction coefficient and the occurrence of peeling of the friction layer.
[0112] It can be seen from Comparative Example 1 that by directly siliconizing without prior laser treatment, the number of triangular friction layer units in the prepared friction layer increases significantly, the triangular friction layer units and the four-corner friction layer units are irregularly distributed, the friction coefficient fluctuates in a large range, and the friction layer peels off.
[0113] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.
Claims
1. A carbon-ceramic brake disc with a friction layer, the carbon-ceramic brake disc with a friction layer comprising a base layer and a friction layer arranged on the outer surface of the base layer, characterized in that: The friction layer surface has a plurality of cracks, and adjacent cracks are interconnected to form a friction layer unit. The friction unit includes a triangular friction layer unit and a quadrangular friction layer unit. The triangular friction layer unit is formed by three interconnected cracks, and the quadrangular friction layer unit is formed by four interconnected cracks. The area of the triangular friction layer unit is 2-15mm 2 The area of the four-corner friction layer unit is 5-20mm 2 .
2. The carbon-ceramic brake disc with friction layer as claimed in claim 1, characterized in that: The number of the triangular friction layer units accounts for 5-30% of the total number of friction layer units, and the number of the quadrangular friction layer units accounts for 70-95% of the total number of friction layer units.
3. The carbon-ceramic brake disc with friction layer as claimed in claim 1, characterized in that: The friction layer has a thickness of 0.5-3 mm.
4. The carbon-ceramic brake disc with friction layer as claimed in claim 1, characterized in that: The width of the crack is 10-100 μm.
5. The carbon-ceramic brake disc with friction layer as claimed in claim 1, characterized in that: The friction layer contains coarse silicon carbide particles with a particle size of 80-150 microns and fine silicon carbide particles with a particle size of 0.5-30 microns, and the content ratio of the coarse silicon carbide particles to the fine silicon carbide particles is 1:1 to 10:
1.
6. The carbon-ceramic brake disc with friction layer as claimed in claim 5, characterized in that: The silicon carbide content in the friction layer is 50-80%, and the silicon content is 20-50%.
7. A method for preparing a carbon-ceramic brake disc containing a friction layer, for preparing a carbon-ceramic brake disc containing a friction layer as claimed in any one of claims 1 to 6, characterized in that: The steps include: S1: preparing a carbon fiber preform of a predetermined thickness; S2: impregnating the carbon fiber preform in 40% phenolic resin, and then drying the carbon fiber preform to obtain an impregnated body; S3: Carbonizing the impregnated body to obtain a carbonized body, the carbonization temperature is 800-1100° C., and the temperature is kept for 4-6 hours; S4: subjecting the carbonized body to low-temperature graphitization treatment in nitrogen to obtain a graphitized body, the treatment temperature is 1400-1800° C., and the temperature is kept for 2 hours; S5: mixing silicon carbide and phenolic powder evenly to obtain friction layer pressed powder, evenly laying the powder on the graphitized body, and then pressurizing at a pressure of 0.5-4 MPa and a temperature of 150° C. for 60 minutes to completely solidify the powder to obtain a brake disc preform; S6: laser engraving the friction layer solidified on the surface of the brake disc preform according to a desired pattern, with an engraving depth of 0.05-0.2 mm, and after engraving, machining to obtain a brake disc preform; S7: placing the brake disc blank into a boron nitride crucible, and then placing it into a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the boron nitride crucible is pre-placed with pure silicon powder 1.1 times the mass of the brake disc blank, the siliconizing treatment temperature is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa; S8: performing surface grinding and outer contour dimension processing on the siliconized body to obtain the carbon-ceramic brake disc containing the friction layer.
8. The method for preparing a carbon ceramic brake disc containing a friction layer according to claim 7, characterized in that: The method for preparing the carbon fiber preform comprises: stacking the carbon fiber unidirectional cloth and the carbon fiber web as a unit layer, wherein the carbon fiber directions of the carbon fiber unidirectional cloth of two adjacent unit layers are at an angle of 90 degrees, and after stacking one unit, acupuncture is performed on the sample, and the unit layers are repeatedly stacked to obtain a carbon fiber preform of a desired thickness, wherein the acupuncture density is 50-200 needles / cm 2 .
9. The method for preparing a carbon ceramic brake disc containing a friction layer according to claim 7, characterized in that: Step S2 and step S3 are performed at least once, so that the density of the carbonized body reaches 1.25-1.45 g / cm 3 .
10. The method for preparing a carbon ceramic brake disc containing a friction layer according to claim 7, characterized in that: The particle size of silicon carbide in the friction layer pressed powder is 80-150 microns, the content is 45-75 vol%, and the phenolic powder is 25-55 vol%.
